Nanoscale mechanical control of surface electrical properties of manganite films with magnetic nanoparticles. Issue 5 (6th March 2019) - Vasić, Borislav; Konstantinović, Zorica; Pannunzio-Miner, Elisa; Valencia, Sergio; Abrudan, Radu; Gajić, Radoš; Pomar, Alberto
Abstract : Mechanical control of electrical properties in complex heterostructures, consisting of magnetic FeO x nanoparticles on top of manganite films, is achieved using atomic force microscope (AFM) based methods. Abstract : Mechanical control of electrical properties in complex heterostructures, consisting of magnetic FeO x nanoparticles on top of manganite films, is achieved using atomic force microscope (AFM) based methods. Under applied pressure of the AFM tip, drop of the electrical conductivity is observed inducing an electrically insulating state upon a critical normal load. Current and surface potential maps suggest that the switching process is mainly governed by the flexoelectric field induced at the sample surface. The relaxation process of the electrical surface potential indicates that the diffusion of oxygen vacancies from the bulk of the manganite films towards the sample surface is the dominant relaxation mechanism. The magnetic FeO x nanoparticles, staying attached to the sample surface after the rubbing, protect the underlying manganite films and provide stability of the observed resistive switching effect. The employed mechanical control gives a new freedom in the design of resistive switching devices since it does not depend on the film thickness, and biasing is not needed.